In vivo single-RNA tracking shows that most tRNA diffuses freely in live bacteria - Plochowietz, A; Farrell, I; Smilansky, Z; Cooperman, B; Kapanidis, A (Oxford University Press, 2016)
Transfer RNA (tRNA) links messenger RNA nucleotide sequence with amino acid sequence during protein synthesis. Despite the importance of tRNA for translation, its subcellular distribution and diffusion properties in live cells are poorly understood. Here, we provide the first direct report on tRNA diffusion localization in live bacteria. We internalized tRNA labeled with organic fluorophores into live bacteria, applied single-molecule fluorescence imaging with single-particle tracking and localized and tracked single tRNA molecules over seconds. We observed two diffusive species: fast (with a diffusion coefficient of ∼8 μm2/s, consistent with free tRNA) and slow (consistent with tRNA bound to larger complexes). Our data indicate that a large fraction of internalized fluorescent tRNA (>70%) appears to diffuse freely in the bacterial cell. We also obtained the subcellular distribution of fast and slow diffusing tRNA molecules in multiple cells by normalizing for cell morphology. While fast diffusing tRNA is not excluded from the bacterial nucleoid, slow diffusing tRNA is localized to the cell periphery (showing a 30% enrichment versus a uniform distribution), similar to non-uniform localizations previously observed for mRNA and ribosomes.